(untitled) (Research, Society and Development, 2020)
Objective: To analyze the association of demographic, clinical factors and lactate levels, with the severity and outcome of sepsis. Method: A cohort study, involving 1184 patients from a university hospital in Porto Alegre / Rio Grande do Sul, Brazil. Data collection took place through active search and medical records of patients with sepsis, from 2013 to 2015. Result: 59.7% (707) came from the emergency, with 2.0 ± 1.39 comorbidities due to with a similar distribution between men and women. Sepsis affected most of the patients, but mostly for septic shock, with respiratory as the main focus. Serum lactate levels (greater than 4 mmol / l) resulted in higher mortality and less than 6% had the lactate recovered until the sixth hour. Conclusion: Demographic and clinical factors that were associated with severity and outcomes were the origin and lactate collection in up to 3 hours. Lactate once again showed that it is an important marker of severity for septic patients, it should not be a marker used only in septic shock, but in cases of suspected sepsis. Sepsis care is of fundamental importance from diagnosis to treatment.